PEDAGOGICAL FOUNDATIONS OF SYSTEMATIC ANALYSIS IN IMPROVING THE EDUCATIONAL PROCESS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article provides insights into the pedagogical foundations of systematic analysis in improving the educational process, and comprehensively covers the role and importance of systematic analysis in implementing the requirements of the state for the development of the education system today and in further developing the education system.